Sprout branches out - Von Innerebner, Jessika (New York Roaring Brook Press, 2023)
Pulling up her roots to find what she needs to thrive, Sprout the plant quickly learns that what she really needs may not be what she thought at all.
2.3.
K-3
Keywords: Plants -- Juvenile fiction; Home -- Juvenile fiction; Self-realization -- Juvenile fiction; Plants -- Fiction; Home -- Fiction; Self-realization -- Fiction; Picture books